Polarization operator of phonons in quadratic approximation - Grigorchuk, N.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Using the method of the retarded Green function the polarization operator of phonons has been calculated with the simultaneous account for the linear and quadratic terms in the Hamilton operator of exciton-phonon interaction. It is shown that at high temperatures and concentrations of excitons the quadratic term may play as important role as linear one.